(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2019)
In Poland, as well in the East European countries, puppet theatres of the second half of the 20th century, and it seems that also in that of the first quarter of the 21st century, the most important person is a director. Was it always so that puppet theatre equals the director? So, the objectives of this study is to determine this problem. It was only in the beginning of 20th century, in the period of the great reform of theatre, that the director was given unlimited competencies. In puppet theatre this process lasted much longer, because the classical style of theatre organization, derived from unaccompanied and private enterprises of particular creators, also endured for longer. Today, it is a director who rules supreme in a puppet theatre. In practice, Polish directors are still convinced today that theatre is intended to tell stories. is process limited puppetry as an independently existing art based primarily on the abilities of the craftsmen; on the miracle of animating a lifeless object, a puppet, whose magical life has so much to offer the spectators. On the contrary, axis of this process stand the artists who see the meaning of their theatrical expression in bring lifeless matter to life. This – when puppet theatre is, after all, a show; it is visual art in motion, not storytelling.